Réponses

  • Utilisateur Brainly
2014-04-14T19:29:13+02:00
A= 3(7X-3)=2(5-3X)
B=X(au carré)+7(X-4)
C=(7X-3)2=4X
D= 2X=7X+72+2(X+5)

Voila pour simplifier t'enlève les fois et tu fais le calcul si besoin
2014-04-14T19:31:45+02:00

 Bonjour ,

A : 3* (7X - 3) = 2* (5 - 3X)
A : 21x -9 = 10-6x

A : 21x+6x = 10+9

A: 27x=19

A: x=19 /27
B :X * X + 7 * (X - 4)

B : x² +7x -28

C :(7X - 3) * 2= 4X

C : 14x -6 = 4x

C : 14x -4x =6

C: 10x = 6

C: x = 6/10

C: x =3/5
D :X * 2 = 7* X + 8 * 9 + 2 * (X + 5)

D : 2X = 7x +72 +2x +10

D: 2x -7x -2x = 72+10

D : -7x = 82

D : x = - 82/7